2003
DOI: 10.1177/0891988703256051
|View full text |Cite
|
Sign up to set email alerts
|

HSP70-2 (HSPA1B) is Associated with Noncognitive Symptoms in Late-Onset Alzheimer's Disease

Abstract: Neuropsychiatric manifestations are common in Alzheimer's disease (AD) and their phenotypic expression might be related to physiopathological and genetic causes. Multiple studies have implicated oxidative stress to the pathogenesis and possible etiology of AD. One of the mechanisms to protect cells from oxidative stress is the expression of heat-shock proteins (HSP). HSPA1B (alternatively known as HSP70-2) has been related to AD pathophysiology. In the present analysis, 77 AD patients were classified according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…It is also involved in the ubiquitin-proteasome pathway. This finding is consistent with our previous association study about associations between Hsp and SZ [1] , and with other findings in the literature, both focused on SZ [53,54] and on other neurological disorders, such as the positive correlation between HSPA1B variations and noncognitive symptoms in patients suffering from Alzheimer's disease [55] . This further evidence of association between SZ and HSPA1B strengthens the hypothesis that this Hsp might be involved in the pathophysiology of SZ.…”
Section: Discussionsupporting
confidence: 82%
“…It is also involved in the ubiquitin-proteasome pathway. This finding is consistent with our previous association study about associations between Hsp and SZ [1] , and with other findings in the literature, both focused on SZ [53,54] and on other neurological disorders, such as the positive correlation between HSPA1B variations and noncognitive symptoms in patients suffering from Alzheimer's disease [55] . This further evidence of association between SZ and HSPA1B strengthens the hypothesis that this Hsp might be involved in the pathophysiology of SZ.…”
Section: Discussionsupporting
confidence: 82%
“…There are only a few investigations regarding the possible role of hsp70-2 in some diseases; for example, BougachaElleuch et al (2000) indicated that there was lack of association between hsp-2 polymorphism and autoimmune thyroid diseases. Clarimon et al (2003) found that the severity of behavioral disturbances in patients with Alzheimer's disease carrying 1 or 2 hsp70-2 deletion alleles was higher for those patients carrying the hsp70-2 insertion. Fekete et al (2003) reported that the hsp70-2 GG genetic variation was associated with low inducibility of HSP70 and with the increased risk of acute renal failure in very low birth weight neonates.…”
Section: Discussionmentioning
confidence: 93%
“…The possible role of HSP70-2 gene polymorphism in various diseases has been reported previously [20][21][22][23]. Although this polymorphism does not alter the amino acid sequence of HSP70-2 protein, previous studies have shown that different genotypes of HSP70-2 are associated with different levels of mRNA expression [22].…”
Section: Discussionmentioning
confidence: 94%